Brown fat and a short circuit make warm and slim - Manfred Doepp (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
It is not widely known that the body contains a mechanism that protects against cold and at the same time leads to normal body weight. It is brown fat, combined with a special protein called thermogenin/UCP1. Though there are several UnCoupled Proteins, the main one for the brown tissue is UCP1. It switches ATP production towards heat production. Good oils and cool outside temperatures help in this process.